Conductive TiN thin films grown by plasma-enhanced atomic layer deposition: Effects of N-sources and thermal treatments - Badie, Clémence; Tissot, Héloïse; Sciacca, Beniamino; Barr, Maissa; Bachmann, Julien; Vallée, Christophe; Gautier, Gaël; Defforge, Thomas; Astie, Vincent; Decams, Jean Manuel; Bechelany, Mikhael; Santinacci, Lionel (Journal of Vacuum Science & Technology A, 2023)
This work consists of optimizing TiN plasma-enhanced atomic layer deposition using two different N-sources: NH3 and N2. In addition to maximizing the growth per cycle (GPC) and to shorten the deposition duration, comprehensive in situ and ex situ physicochemical characterizations give valuable information about the influence of the N-source nature, their dilution in Ar, and the plasma power on layer's final properties. N2 and NH3 dilutions within Ar are extensively investigated since they are critical to decreasing the mean free path (ℓ) of plasma-activated species. A 1:1 gas ratio for the N-sources:Ar mixture associated with low flows (20 sccm) is optimal values for achieving highest GPCs (0.8 Å/cycle). Due to lower reactivity and shorter ℓ of the excited species, N2 plasma is more sensitive to power and generator-to-sample distance, and this contributes to lower conformality than with NH3 plasma. The resistivity of the initial amorphous films was high (≥ 1000 μ ω cm) and was significantly reduced after thermal treatment (≤ 400 μ ω cm). This demonstrates clearly the beneficial effect of the crystallinity of the film conductivity. Though N2 process appears slightly slower than the NH3 one, it leads to an acceptable film quality. It should be considered since it is nonharmful, and the process could be further improved by using a reactor exhibiting optimized geometry.
CRIS-Team Scopus Importer:2023-03-24